The Biopolitics of the Body with Disabilities: How Dual Stigma Controls Accessibility and Shapes the Subjectivity of Persons with Disabilities in Public Spaces - Hariashari Rahim; Putu Wijangga; Risma Risma (Yayasan Literasi Sains Indonesia, 2025)
Background: Urban public spaces are essential for the social participation of persons with disabilities. However, accessibility is often hampered, not just a matter of facilities, but of the biopolitical forces that construct